Dosimetric performance of continuous EPID imaging in stereotactic treatment conditions. (October 2020) - Barbeiro, Ana Rita; Parent, Laure; Vieillevigne, Laure; Ferrand, Regis; Franceries, Xavier
Highlights: aS1000 EPID continuous mode showed to be feasible for stereotactic applications. EPID response in continuous mode showed to be similar to the integrated one. Continuous mode linearity with arc fields is independent of dose rate variations. Continuous acquisition requires higher SDD than the integrated to avoid saturation. Abstract: Purpose: This study aims at investigating the dosimetric characteristics of a Varian aS1000 EPID, focusing on its continuous acquisition mode under the challenging conditions that can be met in stereotactic radiotherapy verification. Methods: An aS1000 EPID installed on a Varian TrueBeamSTx was irradiated with 6 and 10 MV unflattened and flattened photon beams. In order to avoid detector saturation, the source-to-detector distance (SDD) was set to 150 or 180 cm depending on the dose rate. EPID image sets were acquired in continuous mode (CM) and also in the commonly used integrated mode (IM) for comparison, to evaluate dose linearity (including dose rate dependence), repeatability, reproducibility, stability, ghosting effect and field size dependence. Results: CM response linearity was found to be within 0.8% of IM and independent of dose rate. Response repeatability was slightly better for IM and FF beams, being in all cases within 0.9%. Reproducibility was within 0.6% for both modes and all beam qualities. Response stability between continuous frames varied within 1% for dynamic and static irradiations and for all the beam qualities, showing its independence from these parameters. Ghosting effect was not significant, being comparable to signal variations between continuous frames (±1%). Field size dependence in both modes agreed within 1%. Conclusions: The dosimetric response of the aS1000 EPID in CM with FFF beams and high dose rates is comparable to that in IM and for flattened beams provided that the appropriate SDD is used. aS1000 EPID in continuous acquisition mode is therefore suitable for stereotactic applications.